Fragile X Syndrome knowledge from hearing and language teachers and speech therapists in the Region of Murcia - Peñalver-García, Dolores María; García-Sánchez, Francisco Alberto (Revista de Investigación en Logopedia, 2021)
Fragile X syndrome is the principal hereditary cause of intellectual disability and the second genetic cause after Down syndrome. It is caused by a mutation in the FMR1 gene found in the long arm of the X chromosome. Its phenotype is very varied, presenting characteristic physical aspect and behavioral problems related to hyperactivity and social anxiety. An area usually affected during the child’s development is language, in all its dimensions, showing its own characteristics in each of them. Therefore, these children are always cared for by speech therapists and hearing and language teachers, in whom extensive knowledge of the characteristics of the syndrome would be disposable., This study analyzes whether language professionals have this knowledge. In order to do this, an instrument was designed to collect information on training and experience with SXF and assess the professional’s knowledge of some of its most common characteristics. The instrument was completed, voluntarily online, by 35 hearing and language teachers and 49 speech therapists. The results obtained of both professional groups were compared according to variables such as previous experience with SXF or training in it. Both groups of professionals present important concerns in their knowledge about these characteristics of the SXF, we did not find specific differences between teachers and speech therapists. In addition, it is verified that the training received improves knowledge about the SXF.